High performance computer applications : 6th International Conference, ISUM 2015, Mexico City, Mexico, March 9-13, 2015, revised selected papers /: 6th International Conference, ISUM 2015, Mexico City, Mexico, March 9-13, 2015, revised selected papers. (2016) - Unknown
No abstract available